2016
DOI: 10.3389/fmicb.2016.00140
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione-8 Alters Symbiotic Relationship in C. albicans-S. mutans Dual Species Biofilm

Abstract: The small molecule, thiazolidinedione-8 (S-8) was shown to impair biofilm formation of various microbial pathogens, including the fungus Candida albicans and Streptococcus mutans. Previously, we have evaluated the specific molecular mode of S-8 action against C. albicans biofilm-associated pathogenicity. In this study we investigated the influence of S-8 on dual species, C. albicans-S. mutans biofilm. We show that in the presence of S-8 a reduction of the co-species biofilm formation occurred with a major effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 61 publications
(85 reference statements)
8
51
0
Order By: Relevance
“…Some of the bacterial species 531 experienced a reduced growth due to competition in the untreated multispecies biofilm, while 532 antimicrobial treatment restored their growth in the multispecies biofilm to the level of the untreated 533 monoculture biofilms. In contrast, but also consistent with our rationale, a reduction in antimicrobial 534 tolerance under multispecies conditions has been explicitly associated with a reduction of (probably 535 rare) cooperative inter-species interactions (Feldman et al, 2016). 536 In our final model, we found that the presence of competitors can also directly enhance the 537 inherent tolerance of other species by driving specific tolerance phenotypes.…”
Section: Direct Effect Of Competitors On Antimicrobial Tolerance 398supporting
confidence: 80%
See 2 more Smart Citations
“…Some of the bacterial species 531 experienced a reduced growth due to competition in the untreated multispecies biofilm, while 532 antimicrobial treatment restored their growth in the multispecies biofilm to the level of the untreated 533 monoculture biofilms. In contrast, but also consistent with our rationale, a reduction in antimicrobial 534 tolerance under multispecies conditions has been explicitly associated with a reduction of (probably 535 rare) cooperative inter-species interactions (Feldman et al, 2016). 536 In our final model, we found that the presence of competitors can also directly enhance the 537 inherent tolerance of other species by driving specific tolerance phenotypes.…”
Section: Direct Effect Of Competitors On Antimicrobial Tolerance 398supporting
confidence: 80%
“…Indeed, incomplete 496 inhibition of a network of cooperating species is expected, not to promote, but to pull down the 497 remaining species because of abrogation of positive feedback loops, as is motivated by recent 498 ecological network studies (Coyte et al, 2015). This would reduce, not increase, the overall tolerance 499 of the multispecies biofilm (Feldman et al, 2016). Our models only provide examples of multispecies 500 biofilms in which specific species strongly suppress other species.…”
Section: Direct Effect Of Competitors On Antimicrobial Tolerance 398mentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, incomplete inhibition of a network of cooperating species is expected, not to promote, but to pull down the remaining species because of abrogation of positive feedback loops, as is indicated by recent ecological network studies [84]. This would reduce, not increase, the overall tolerance of the multispecies biofilm [80]. Our models only provide examples of duo-species or multispecies biofilms in which specific species strongly suppress other species.…”
Section: Discussionmentioning
confidence: 67%
“…In most of these studies the enhanced tolerance was attributed to protective effects of the species on each other, however, generally without unraveling the mechanism of tolerance. In contrast, a minority of studies did not observe an effect of multispecies conditions on antimicrobial tolerance [79] or measured a decrease in tolerance in multispecies conditions [63,[80][81][82][83].…”
Section: Discussionmentioning
confidence: 98%